2010
DOI: 10.1063/1.3333538
|View full text |Cite
|
Sign up to set email alerts
|

Islands in the stream: The effect of plasma flow on tearing stability

Abstract: Reducing plasma flow clearly decreases the stability of tearing modes in multiple regimes (sawtooth, hybrid) in both high- and low-aspect-ratio tokamaks (DIII-D [J. L. Luxon, Nucl. Fusion 42, 614 (2002)], Joint European Torus [M. Keilhacker and the JET Team, Plasma Phys. Controlled Fusion 41, 301 (1999)], National Spherical Torus Experiment [M. Ono, S. M. Kaye, Y.-K. M. Peng, Nucl. Fusion 40, 557 (2000)], each with distinct means of lessening rotation). Further, reducing flow makes pre-existing “saturated” isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 44 publications
6
97
2
Order By: Relevance
“…This disagrees with the experiments at DIII-D, where a further decrease of the onset threshold with counter rotation was found. As already mentioned in previous works it was suggested that an offset of the threshold minimum exists which was not reached at DIII-D [1]. According to [23] the correct parameter to investigate the dependence of the NTM threshold on rotation is the velocity of the island in the laboratory frame f NTM,lab , where the local radial electric field E r is zero.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This disagrees with the experiments at DIII-D, where a further decrease of the onset threshold with counter rotation was found. As already mentioned in previous works it was suggested that an offset of the threshold minimum exists which was not reached at DIII-D [1]. According to [23] the correct parameter to investigate the dependence of the NTM threshold on rotation is the velocity of the island in the laboratory frame f NTM,lab , where the local radial electric field E r is zero.…”
Section: Resultsmentioning
confidence: 99%
“…From this discrepancy one can infer that there exists an influence of plasma rotation on the underlying tearing stability. This means that at lower plasma rotation the ∆ ′ term changes such that the plasma is less stable against NTMs as already proposed in [7] and [1]. Further investigations have been made to disentangle the influence of rotation on the island stability itself as opposed to the trigger mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, flow shear at the rational surface is shown to make the effective tearing stability index ∆ more negative. 6,7 In the theoretical aspect, both analytical and numerical studies have been carried out. In the linear phase and in the slab geometry, plasma flow shear is found to either increase or decrease the linear growth rate, depending on the plasma viscosity, the magnetic shear and the strength of flow shear.…”
Section: Introductionmentioning
confidence: 99%